Commentaries on Technology - Taylor, T. Ajibola; Mupawose, Robbie M.; Collinson, Michael (International Food Policy Research Institute, 1987)
The preceding chapter focuses on food production systems in four broad agroecological zones in which agroclimatic conditions and the characteristics of production systems largely determine the types of technologies likely to have measurable impact on agricultural production. Population pressure in these areas makes it impossible for the traditional, balanced farming systems characterized by shifting cultivation to meet demand for food and other requisites.